Brewing Science: A Multidisciplinary Approach - Mosher, Michael; Trantham, Kenneth (Springer, 2017)
What do your professors do at the end of a day at college? Many, the authors included, will enjoy a craft brew and discuss the day’s successes and opportunities for improvement. Thus began the discussion for the beginnings of this book. “Wouldn’t it be awesome,” we thought, “if we could highlight the science that goes into brewing? The students would just love a brewing science class!” We spent the next weeks and months designing and planning a course that would illustrate the interdisciplinary nature of brewing science. The result is what you will find here. This text represents the topics that are taught in our courses on an Introduction to Brewing. These courses are very popular at our institutions and attended by students from almost every major. We have tried to write from your perspective and provide not only the processes that you will encounter in the brewery, but also provide the reasons why those processes are completed and the science behind them. And we have written the text with no assumptions as to what courses you have previously taken. As topics are introduced, we also introduce the science behind them starting from the basics. As we have found, teaching “just in time” provides useful examples for you to use to help you understand the background and the topic in question. Every few pages, you will find CHECKPOINT boxes. These are designed to provide you with a chance to take a break and confirm that you have gathered the key topics of the discussion to that point. This is also how we have constructed the images that accompany the discussion. When images and tables appear in the text, it is important to take a break from reading and examine them in detail. Understand why each is included in the chapter, and why each is presented in the way it is. (Some professors, the authors included, find great quiz and test questions by looking at the figures.)